2018
DOI: 10.1089/g4h.2017.0165
|View full text |Cite
|
Sign up to set email alerts
|

Moderator Roles of Optimism and Weight Control on the Impact of Playing Exergames on Happiness: The Perspective of Social Cognitive Theory Using a Randomized Controlled Trial

Abstract: Exergames can maintain happiness among users, and such maintenance can be the strongest among users who are trying to control their weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Two of these, conducted with adult participants and featuring analogous experimental conditions (30 min, one weekly session over 2 weeks) using the game “Your Shape: Fitness Evolved,” registered a substantial elevation in happiness levels ( 39 , 43 ). In a study with children, Nguyen et al ( 51 ) found that Exergames notably raised levels of happiness, displaying particularly pronounced results in children under weight management. Intriguingly, the same study did not detect a moderating effect on optimism levels ( 51 ), possibly hinting at a specific correlation between the enhancement in happiness and the weight control aspect of exergaming, without necessarily extending to future outlook and optimism regarding the benefits of practice.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these, conducted with adult participants and featuring analogous experimental conditions (30 min, one weekly session over 2 weeks) using the game “Your Shape: Fitness Evolved,” registered a substantial elevation in happiness levels ( 39 , 43 ). In a study with children, Nguyen et al ( 51 ) found that Exergames notably raised levels of happiness, displaying particularly pronounced results in children under weight management. Intriguingly, the same study did not detect a moderating effect on optimism levels ( 51 ), possibly hinting at a specific correlation between the enhancement in happiness and the weight control aspect of exergaming, without necessarily extending to future outlook and optimism regarding the benefits of practice.…”
Section: Resultsmentioning
confidence: 99%
“…Internal validity could be better justified by using experimental designs, e.g. randomized controlled trials (Nguyen et al , 2018). Therefore, future studies can choose to use such trials to provide strong evidence.…”
Section: Discussionmentioning
confidence: 99%
“…That is, volunteers are randomly assigned to join groups formed independently and before the onset of the study. Group-based intensive lifestyle interventions have demonstrated an ability to increase weight loss among participants (Mayer-Davis et al, 2004), but these effects have been shown to be moderated by personal characteristics such as optimism (e.g., Scheier & Carver, 1992; Van Nguyen et al, 2018). Optimism represents an individual-level continuous moderator that plausibly varies across groups under this design because the intervention groups were formed prior to assignment.…”
Section: Treatment Assignment To Extant Nesting Structurementioning
confidence: 99%